Determinasi Tingkat Kemiskinan di Kabupaten/Kota Provinsi Aceh - Muttaqien; Iqbal; Maisyuri; Fauzan; Shalawati; Ulfia Rahmi; Eliza Nopita (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Poverty is a classic topic of discussion but interesting because the problem of poverty has not been resolved. This study analyzes the role of the human development index, GRDP and unemployment on the poverty rate in the Districts/Cities of Aceh Province. Using the panel data analysis method with time series for 2018-2022 and cross sections of 23 districts/cities in Aceh province. The results showed that GRDP and unemployment had a positive effect on the poverty rate, but the HDI had no effect on the poverty rate. Thus, it can be said that the government must strive to reduce inter-regional disparities, support labour-intensive, targeted, and direct investments in the real sector, and involve all stakeholders.